The impact of the educational level of the family on the lifestyle of children before and during the COVID-19 pandemic - Nazim Myrtaj; Mimoza Moza Shkodra; Eglantina Bilalli; Arben Maliqi; Blerim Sylejmani (Kazimierz Wielki University, 2021)
The lifestyle of children is most affected by the family, which is defined as a basic social community based on the common life of a close circle of blood relatives, usually parents and children, in which biological-reproductive, economic and education functions are combined. The purpose of the research is to confirm the impact of the educational level of parents on the lifestyle of their children before and during the COVID-19 pandemic. The research included 110 students of both genders from SHMT "Mehmet Isai" and SHMAT "Arbëria" in Gjilan divided into two groups of 55 students, according to the educational level of their parents. The lifestyle survey included 8 questions on physical activity, daily cigarette consumption, alcohol, drug use, eating habits and sleep before and during COVID -19 pandemic. To verify the difference between the groups, the Chi-square test (χ² test) was applied. Survey analysis shows that children of parents with higher educational level have more knowledge about the role of physical activity and spend more time on physical activity, consume less cigarettes and alcohol and more regular eating and sleeping habits at the level p<0.00. We can conclude that the educational level of the parents has a significant impact on the motivation of children to engage in physical activity, reducing the consumption of cigarettes and alcohol, for sleep and regular nutrition.